Pro-Oxidative Action of Polyphenols as Action Mechanism for their Pro-Apoptotic Activity - Marina Lecci, Raffaella; Logrieco, Antonio; Leone, Antonella (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Polyphenols, secondary metabolites widely present in plant kingdom, are known for their positive effects on human health, such as treatments of degenerative disease and cancer. Many dietary polyphenols show anti-inflammatory, immunomodulatory and antioxidant properties and they are proposed as chemopreventive agents for many skin disorders and cancer. Exposure to solar UV radiation is widely considered to cause skin cancer and a consistent carcinogenic dose derived from UVA causes several skin disorders as a consequence of free radicals generation and DNA damages. In this study, verbascoside, isoverbascoside and tyrosol were investigated for their effects on HEKa (Human Epidermal Keratinocytes adult) cell cultures challenged from UVA-rays. Non-toxic doses of each polyphenol were assayed on HEKa before, during and after the exposure to a damaging dose of UVA. Treatment with polyphenols before and after the UVA-irradiation exerted a pro-oxidant effect, while the simultaneous treatment caused a weak decrease of ROS production. The increasing of ROS levels was associated with a proapoptotic effect on HEKa, detected by AnnexinV/Propidiun Iodide, mainly evident in surviving cells treated with the polyphenols after the UVA-irradiation. The pro-apoptotic effect was confirmed by the immunodetection of significant changes in the Bax and Bcl-xL protein levels, leading to apoptotic events. The hypothesis that these polyphenols could trigger the apoptosis pathway mainly in UVA-damaged cells, via ROS increase, is here proposed as action mechanism behind their protective effect.
Keywords: Apoptosis